Extremely high sulfate reduction, sediment oxygen demand and benthic nutrient flux associated with a large-scale artificial dyke and its implication to benthic-pelagic coupling in the Yeongsan River estuary, Yellow Sea. Issue 1 (15th July 2017) - Kim, Sung-Han; Lee, Jae Seong; Hyun, Jung-Ho
Abstract: We investigated environmental impact of large-scale dyke on the sediment geochemistry, sulfate reduction rates (SRRs), sediment oxygen demand (SOD) and potential contribution of benthic nutrient flux (BNF) to primary production in the Yeongsan River estuary, Yellow Sea. The sediment near the dyke (YE1) with high organic carbon (Corg ) content (> 4%, dry wt.) was characterized by extremely high SOD (327 mmol m − 2  d − 1 ) and SRRs (91–140 mmol m − 2  d − 1 ). The sulfate reduction accounted for 73% of Corg oxidation, and was responsible for strikingly high concentrations of NH4 + (7.7 mM), PO4 3 − (67 μM) and HS − (487 μM) in pore water. The BNF at YE1 accounted for approximately 200% of N and P required for primary production in the water column. The results present one of the most extreme cases that the construction of an artificial dyke may have profound impacts on the biogeochemical and ecological processes in coastal ecosystems. Highlights: The impacts of an artificial dyke on the sediment biogeochemistry were investigated. The deposition of organic matter near the dyke stimulated microbial metabolism. Sulfate reduction (SR) near the dyke accounted for 73% of total carbon oxidation. High SR was responsible for the extremely high N, P & HS − levels in pore water. Benthic nutrient release explained 200% of the N & P required for primary production.